NIEWYDOLNOŚĆ SERCA I PŁUC, TRANSPLANTOLOGIAGiant cell myocarditis in the explanted heart of an orthotopic heart transplant recipient – a case report - Krynicka, Anna; Nożyński, Jerzy; Zakliczyński, Michał; Konecka-Mrówka, Dominika; Przybylski, Roman; Zembala, Marian (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2009)
Giant cell myocarditis (GCM) is an unusual cause of cardiomyopathy. Because of its fulminant clinical course and specific treatment, it should be taken into consideration in patients with a new onset of left ventricular heart failure, which is difficult to treat with standard therapy. Giant cell myocarditis may present as an atrioventricular block as well. The outcome is fatal, unless the patient undergoes a heart transplantation. Mean survival time from the first symptoms to end-point (transplantation or death) is 5.5 months. We would like to present a case of a patient who was successfully treated with heart transplantation for cardiomyopathy caused by GCM, which was revealed in the explanted heart.